Ambiguity as Principle - Andreas W. Daum (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2025)
This article investigates Alexander von Humboldt’s position vis-à-vis the German revolution of 1848 and illuminates the different roles that scientists played in the public arena. Humboldt never committed himself to any political ideology or national movement. Instead, he maintained ambiguity as a social strategy and guiding principle to navigate through the revolutionary turmoil, interact with people of different political opinions, and stay true to his scholarly priorities. With great caution, Humboldt signaled his support for a constitutional monarchy and civil rights while remaining fearful of radical regime changes and violence. Retrospective attributes such as ‘democratic’ and ‘republican’ miss the ambiguity in his political stance and his loyalty to the Prussian king. Humboldt’s understanding of politics remained personalized and reserved; it was situational and bound to conversational settings.